Eye position affects the perceived location of touch. - Harrar, V; Harris, L (2009)
Here, we demonstrate a systematic shift in the perceived location of a tactile stimulus on the arm toward where the eye is looking. Participants reported the perceived position of touches presented between the elbow and the wrist while maintaining eye positions at various eccentricities. The perceived location of the touch was shifted by between 1 and 5 cm (1.9 degrees -9.5 degrees visual angle) by a change in eye position of +/-25 degrees from straight ahead. In a control condition, we repeat the protocol with the eyes fixating straight ahead. Changes in attention accounted for only 17% of the shift due to eye position. The pattern of tactile shifts due to eye position was comparable whether or not the arm was visible. However, touches at locations along the forearm were perceived as being farther apart when the arm was visible compared to when it was covered. These results are discussed in terms of the coding of tactile space, which seems to require integration of tactile, visual and eye position information.